The Impact of Agricultural Modernization on Economic Development in Maros Regency, South Sulawesi - Afryilia, Mauldya; Yanti, Risma; Marhama, Sitti (Scieclouds Publishing, 2024)
This study investigates the impact of agricultural modernization on economic development in Maros Regency, South Sulawesi. The research analyzes the influence of technological adoption along with farming practice improvements and training/support services toward GDP growth and agricultural employment numbers and farmers' income levels. 200 agricultural stakeholders and secondary government reports were used in a quantitative design to gather data via surveys. The research demonstrates that economic development receives notable contributions from agricultural modernization through technological adoption which proves itself as the most powerful factor that achieves positive changes in all economic indicators. No evidence suggests that agricultural support programs and farming practice enhancements create the same magnitude of positive results on GDP growth and employment as technological adoption. The results from multiple regression analysis revealed that both agricultural technology usage as well as agricultural practice enhancements produced substantial and statistically important positive effects on economic development. This study addresses a literature gap because it presents empirical findings about Maros Regency which previous research studies had neglected. The research delivers essential recommendations to policy makers who should launch enhanced agricultural development programs for achieving sustainable rural growth.